David Busch's Sony [alpha] a7R II/a7 II : guide to digital photography - Busch, David D. (Rocky Nook, 2016)
David Busch's Sony Alpha a7 II/a7 R II Guide to Digital Photography is the much-anticipated comprehensive resource and reference for two of the hottest cameras on the market today. Sony's advanced 24-megapixel mirrorless Alpha a7 II and the ground-breaking 42-megapixel Alpha a7R II combine high-resolution imaging and remarkable low-light performance in the world's smallest full-frame package. Both cameras have fast sensor-based phase detect autofocus and 5-axis in-body image stabilization that adds powerful SteadyShot anti-shake vibration reduction to Sony E-mount and adaptor-mounted A-mount a.